THE ROLE OF ISLAMIC COACHES IN MEDAN JOHOR DISTRICT IN PREVENTING THE DANGERS OF RADICALISM - Ismed Batubara; Yeltriana Yeltriana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This study focuses on the role of Islamic Religious Education instructors specifically for non-PNS PAIs in Medan Johor District in order to prevent the dangers of radicalism. To find out the role of Islamic instructor, a qualitative field research was used (field research) by conducting interviews and literature review. The results of study can explain that Islamic extension agents have played their role in providing religious education to the community. Then there is an obstacle in providing counseling is that there are still a small part of the community who have not been very responsive in understanding the dangers of radicalism. To overcome it, Religious Instructor always provides understanding, enlightenment, and approaches to society